Panicum maximum leaf extract induces reproductive toxicity in adult male Wistar rats - Uchechukwu Iyanyi; Ben Ehigiator; Emmanuel Ifedigbo (Golestan University Of Medical Sciences, 2024)
Background: Many environmental chemicals are implicated in causing serious adverse health effects on the reproductive system. Some medicinal plants taken traditionally for different ailments are particularly toxic to the reproductive organs. This study was undertaken to evaluate the reproductive toxicity of the ethanol leaf extract of Panicum maximum on adult male rats. Methods: The leaves were randomly collected. Ground and powdered leaves were extracted by cold maceration using ethanol. Sixteen adult male rats (130-200 g) were divided into 4 groups. The negative control group (group I) was given 10 mL/kg distilled water, while Group II-IV received 50, 100, and 200 mg/kg of Panicum maximum leaf extract for 21 days. The animals were sacrificed and analyzed for some reproductive parameters at the end of the 21 days. Results: There was a decrease in the body weight of the rats, as well as the testis at 200 mg/kg when compared to the control within the treatment period. Sperm analysis showed a significant decrease in normal sperm cells, sperm variability, active sperm cells, and sperm count in all groups given Panicum maximum leaf extract. There was a significant increase in abnormal and dead sperm cells. Hormonal analysis showed a decrease in follicle-stimulating hormone (FSH) and testosterone (TST) levels, which was significant. The histology of the testis also indicated toxicity of the extract, and it was dose-dependent. Conclusion: Ethanol leaf extract of Panicum maximum is relatively toxic to the male reproductive system.